Paleoenvironmental and Biotic Changes in the Late Triassic of Argentina: Testing Hypotheses of Abiotic Forcing at the Basin Scale - Mancuso, Adriana C.; Irmis, Randall B.; Pedernera, Tomás E.; Gaetano, Leandro C.; Benavente, Cecilia A.; Breeden III, Benjamin T. (Frontiers in Earth Science, 2022)
Paleoenvironmental factors such as climate change are often hypothesized as critical for ecosystem changes over evolutionary time scales. Theoretically, these changes should be observable in the fossil record, but the robust linkage of biotic shifts to climate events remains difficult. The Late Triassic Period is an ideal interval for testing such hypotheses within terrestrial ecosystems because of a number of large-scale climate events, such as the Carnian Pluvial Episode (CPE), and a rich, well-studied fossil record. Nonetheless, at regional to global scales, few linkages have been identified during most of the Late Triassic. Here, we synthesize a multi-proxy basin-scale dataset of paleoenvironmental data, including new information from clay mineralogy and paleosol major- and trace-element geochemistry, to understand paleoclimate changes in the Ischigualasto-Villa Unión Basin of northwestern Argentina. In combination with diversity and relative abundance information from the well-sampled plant and tetrapod fossil record in the basin, we then use accepted evolutionary models of abiotic forcing of changes in ecosystems to test previously proposed hypotheses of floral and faunal variations at a basin scale. We find that although many patterns are best explained by sampling issues and taphonomy, pseudosuchian archosaur and plant diversity and rhynchosaur relative abundance and conform to predictions of paleoenvironmental forcing as the climate changed from warmer, drier conditions to more temperate humid conditions. These data demonstrate how high-resolution multi-proxy data and a well-sampled fossil record at a basin-scale can be used to test hypotheses of abiotic forcing of ecosystems in deep time, and highlights where future efforts should be directed in terms of filling data gaps and testing new hypotheses.